Data Warehouse Model Design PT. Pos Indonesia - Aisyah Norma Ruslita Batubara; M. Aza Raja Darus; Siti Rahmayanti Putri; Widya Ananda; Nurbaiti (Formosa Journal of Computer and Information Science, 2023)
This study aims to determine the role of the data warehouse, data warehouse design, and analyze case studies from the of PT. Pos Indonesia. The data warehouse has an important role for a company in terms of storing and processing data automatically to assist companies in terms of finding data, managing data, making quality decisions and data consistency. As the need for practical data develops and is able to handle data with very large results and display historical data, it is therefore necessary to develop a database for PT. Pos Indonesia. This study is a file design activity from the information provided by the PT. Pos Indonesia. The research method used in this study is a quantitative method which is divided into several stages. The planning phase of the warehouse starts with the subject data warehouse, defines the data source, and steps to implement capabilities to create multidimensional data models in the form of star schemas, snowflake schematics and constellation diagram experts, ETL (Extract, Transform and Load) processes and report analysis. Reporting on the data warehouse information analysis process at the Post Shop PT. Pos Indonesia compiles the best sales information based on product type, the highest sales volume per customer and the highest sales volume based on time. The report analysis results are very useful for making data from 2014 and 2015